Ric1p and Rgp1p form a complex that catalyses nucleotide exchange on Ypt6p - Siniossoglou, Symeon (Oxford University Press, 2000)
Cells lacking the GTPase Ypt6p have defects in intracellular traffic and are temperature sensitive. Their growth is severely impaired by additional mutation of IMH1, which encodes a non-essential Golgi-associated coiled-coil protein. A screen for mutants that, like ypt6, specifically impair the growth of imh1 cells led to the identification of RIC1. Ric1p forms a tight complex with a previously uncharacterized protein, Rgp1p. The Ric1p–Rgp1p complex binds Ypt6p in a nucleotide-dependent manner, and purified Ric1p–Rgp1 stimulates guanine nucleotide exchange on Ypt6p in vitro. Deletion of RIC1 or RGP1, like that of YPT6, blocks the recycling of the exocytic SNARE Snc1p from early endosomes to the Golgi and causes temperature-sensitive growth, but this defect can be relieved by overexpression of YPT6. Ric1p largely colocalizes with the late Golgi marker Sec7p. Ypt6p shows a similar distribution, but this is altered when RIC1 or RGP1 is mutated. We infer that the Ric1p–Rgp1p complex serves to activate Ypt6p on Golgi membranes by nucleotide exchange, and that this is required for efficient fusion of endosome-derived vesicles with the Golgi.